PENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) DAN KERJASAMA ANTAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN MEDIA KOKAMI DI KELAS IV SD NEGERI 2 DUKUHWALUH - Kurniasih, Puji Dwi; Nugroho, Agung; Harmianto, Sri (ATTA`DIB, 2020)
The background of this research was the students’ low Higher Order Thinking Skills and collaboration between students and this research aimed to improve it. This was a classroom action research with two cycles and each cycle consisted of two meetings. The procedure of this research used Kemmis & McTaggart that included planning, acting, observing, and reflecting. The subjects of this research were 27 fourth graders consisting of 17 female and 10 male students. The instruments used test and non-test. The test instrument included the assesment of Higher Order Thinking Skills, while the non-test instruments included observation sheets, interview, and documentation. The data result of student’ Higher Order Thinking Skills in cycle I showed 59,48% completeness and in cycle II improve to 79,20%. Collaboration between student in cycle I showed 63,45% and in cycle II improve to 75,80%. So, it beconcluded that the Problem Based Learning (PBL) model assisted by the KOKAMI media was able to improve the students’ Higher Order Thinking Skills and collaboration between students’ in the fourth grade of SD Negeri 2 Dukuhwaluh.